How to optimise the fidelity of exercises in an unsupervised golf injury prevention programme? A pilot study - Denise Eygendaal; Saskia Gladdines; Leonieke van Boekel; Annechien Beumer (BMJ Open Sport & Exercise Medicine, 2024)
Background Golf is an individual sport that is usually done without the supervision of a trainer or coach. Therefore, an injury prevention programme in golf will primarily be performed without supervision and feedback. However, the effectiveness of any preventive exercise programme is determined by exercise fidelity.Objective To investigate the different instruction options of an injury prevention programme on exercise fidelity in individual golfers.Methods We randomly assigned golfers to one of three groups receiving different exercise instructions. One group received only instructional cards (A), one received only instructional videos (B) and a third group (C) received both instructional cards and videos. The golfers were allowed to familiarise themselves with the exercises based on the provided instruction option, after which we recorded their exercise execution on video. Two authors independently scored each exercise’s fidelity from these recordings.Results In total, 18 golfers (12 women and 6 men, average age of 61.94 years) were equally divided across the 3 study groups completed 108 exercises. In group A 73.7% of exercises were executed as intended, in group B 88.6% and in group C 86.3%. Significantly more exercises were conducted correctly in groups B and C compared with group A (p<0.05).Conclusion Golfers who received instructions that included a video explanation had a higher exercise fidelity when compared to only written instructions.